Clinical and radiological outcomes after stand-alone ALIF for single L5-S1 degenerative discopathy using a PEEK cage filled with hydroxyapatite nanoparticles without bone graft - Norotte, Gilles; Barrios, Carlos (Clinical neurology and neurosurgery, 2018)
•Stand-alone L5-S1 ALIF was evaluated in 65 patients with degenerative disc disease.•ALIF was performed with a PEEK cage filled with hydroxyapatite nanoparticles.•At 2-year follow-up, functional X-rays disclosed a 95.4% fusion rate.•Excellent clinical outcome (Macnab’s criteria) was reported by 75.4% of the patients.•No patient underwent additional surgical procedures during the period of study. Recent improvements in cage designs with integral fixation and screw attachments have made stand-alone ALIF a viable option with several possible advantages. The aim of this study was to confirm the efficacy and safety of a PEEK cage filled with hydroxyapatite nanoparticles without adding a bone graft for stand-alone ALIF in the treatment of L5-S1 isolated degenerative disc discopathy (DDD). Sixty-five patients who required surgery for DDD were evaluated. Clinical outcome evaluations included back and leg pain (VAS), disability (Oswestry Disability Index), and patient satisfaction (Macnab’s criteria). Radiological outcomes include the assessment of disc height, the L5-S1 intervertebral disc angle, and anterior intervertebral fusion through standard and functional sagittal X-rays of the lumbar spine. Clinical and radiological measurements were assessed 2, 6, 12, and 24 months after surgery. Clinical outcomes improved progressively and stabilized from 12- to 24-month follow-up. Final postoperative ODI scores showed a notable improvement (95%CI = 36.1–48.9 points; p < .001). Similarly, 24-month postoperative VAS scores revealed a significant decrease in pain (95%CI = 5.4–6.2; p < .001). The fusion rate was 95.4%. Anterior disc height was restored from 4.1 ± 3.2 mm at baseline to 9.5 ± 1.6 mm in the immediate postoperative period (p < .001). A small collapse (17.9%) of the disc height was detected from the 2- and 24-month follow-ups. Cage subsidence (more than 3 mm collapse) was detected in 4 cases (6.2%) and was related to cage size (more than 11 mm height; P < .05). There were no serious bone substitute-related adverse events and no revision surgeries. Stand–alone anterior lumbar interbody fusion using hydroxyapatite nanoparticles without an autologous bone graft is an effective and safe treatment option for L5-S1 degenerative pathology. Clinical outcomes were very satisfactory with a high fusion rate.